Comparison of sodium ion diffusion between simplexes in different silicate glass systems using molecular dynamics simulations - Pham Thi Lien (Tạp chí Khoa học và Công nghệ)
This study investigates sodium ion (Na⁺) diffusion in sodium silicate glasses Na₂O.mSiO₂ (NSm, m = 1, 2, 3, 4) at 1173K using molecular dynamics simulations. Instead of traditional Radial Distribution Function (RDF) or Coordination Number methods, simplex analysis identifies diffusion pathways, revealing structural dynamics and ion mobility. Key findings include differences in the number of simplexes (NSP), bridging oxygens in a simplex (ZBO), and simplex size (SPS), which significantly affect Na⁺ diffusion. Simplexes with fewer bridging oxygens facilitate Na⁺ movement. Na⁺ ions often leave and return to their original simplex, creating a correlation effect on diffusion. Parameters like mean squared displacement (d²) and average residence time (tₛ) in simplexes are linked to Na⁺ diffusion coefficients, contributing to a better understanding of the Na⁺ diffusion mechanism.